The influence of methamphetamine on maternal behavior and development of the pups during the neonatal period - Ševčíková, Mária; Hrebíčková, Ivana; Macúchová, Eva; Šlamberová, Romana (International journal of developmental neuroscience, 2017)
Since it enters breast milk, methamphetamine (MA) abuse during lactation can not only affect the quality of maternal behavior but also postnatal development of pups. The aim of the present study was to examine the effect of injected MA (5mg/kg) on maternal behavior of rats and the differences in postnatal development, during postnatal days (PD) 1-11, of pups when the pups were directly exposed (i.e., injected) to MA or received MA indirectly via breast milk. Maternal behavior was examined using observation test (PD 1-22) and pup retrieval test (PD 1-12). The following developmental tests were also used: surface righting reflex (PD 1-12), negative geotaxis (PD 9), mid-air righting reflex (PD 17), and the rotarod and beam-balance test (PD 23). The weight of the pups was recorded during the entire testing period and the day of eye opening was also recorded. MA-treated mothers groomed their pups less and returned the pups to the nest slower than control dams. The weight gain of pups indirectly exposed to MA was significantly slower. In addition, pups indirectly exposed to MA were slower on the surface righting reflex (on PD 1 and PD 2) and the negative geotaxis test. In females, indirect exposure to MA led to earlier eye opening compared to controls. At the end of lactation, males who received MA indirectly via breast milk performed worse on the balance beam test compared to males who received MA directly. However, direct exposure to MA improved performance on rotarod relative to controls. Our results suggest that indirect MA exposure, via breast milk, has a greater impact than direct MA exposure.
Keywords: polohový reflex; Analysis of Variance; Prenatal Exposure Delayed Effects; Animals, Newborn; embryo savčí; Male; Rats, Wistar; Psychomotor Performance; zpožděný efekt prenatální expozice; psychomotorický výkon; sexuální faktory; Pregnancy; těhotenství; Sensorimotor development; Age Factors; Embryo, Mammalian; mužské pohlaví; potkani Wistar; mateřské chování; novorozená zvířata; Body Weight; lokomoce; Maternal Behavior; krysa rodu Rattus; Central Nervous System Stimulants; methamfetamin; Reflex, Righting; Maternal behavior; Animals; stimulanty centrálního nervového systému; Locomotion; Methamphetamine; Psychostimulants; ženské pohlaví; analýza rozptylu; zvířata; Sex Factors; Rats; věkové faktory; Neonatal period; Mother-Child Relations; Female; Wistar; tělesná hmotnost; vztahy mezi matkou a dítětem